Penerapan Model Pembelajaran Make A Match Dalam Pengembangan Inovasi Learning Card Terhadap Peningkatan Pengetahuan Mahasiswa Profesi Ners Menghadapi Ujian Kompetensi Nasional¬¬ - Pattimura, Nastain Abubakar; Karno, Yosef Marsianus; Thalib, Abdul (An Idea Health Journal, 2025)
Introduction: Cooperative learning, one of the widely applied active pedagogical methods, aims to improve students' abilities. This approach is based on the concept that learning occurs in a social context, involving interaction between individuals, the environment, and peers. However, research on this active method is still limited, especially in the context of higher education and communication. Research shows that cooperative learning can improve students' social and intellectual development, help them hone their interpersonal skills, and increase their sense of accomplishment, productivity, and psychological well-being. Methods: This study used a quantitative approach with a pre-test and post-test One Group Design experimental design, involving 104 respondents and a total sampling technique. The instruments used for data collection are learning cards and knowledge questionnaires. Results: The study showed a significant difference in students' knowledge before and after applying the "Make a Match" learning model using learning cards, with an average overall score of 3596, a standard deviation of 4654, and a p-value < 0.05. Based on these findings, it can be concluded that the "Make a Match" learning model that uses learning cards is more effective in increasing student knowledge than methods that do not.